Pelaksanaan Pendaftaran Tanah Sistematis Lengkap Berbasis Partisipasi Masyarakat (PTSL+PM), Kendala Dan Solusinya - Winda Sandra Dewi Mambrasar; Senthot Sudirman; Wahyuni Wahyuni (Sekolah Tinggi Pertanahan Nasional, 2020)
PTSL targets are increasing every year. Limited human resources to finish this project make the government issued a policy based on Article 42 paragraph (1) ATR / BPN Regulation No. 6 year 2018 regarding the implementation of PTSL activities that can be carried out based on community participation (PTSL+PM), and Technical Guideline Number: 002 /JUKNIS-300.UK.01.01 /II /2019 dated February 1, 2019 concerning Complete Systematic Land Registration Activities Based on Community Participation (PTSL+PM). This research objectives are: 1) to find out the implementation of PTSL activities involving the community in Ngestiharjo Village, 2) to find out the constraints and solutions in implementing PTSL+PM activities in Ngestiharjo Village, and 3) to find out the benefits of SIAP and SANTRI PTSL+PM applications in the implementation of PTSL+PM activities in Ngestiharjo Village. In conducting this research, the researcher applied qualitative method. The benefit of using the SIAP application is, it facilitates to collection of juridical data in the form of nominative lists and the data integration process. It also produces output in the form of a complete registration file.